Peran Sistem Informasi Rumah Sakit Tentang Unit Logistik Dalam Mendukung Operasional Rumah Sakit Muhammadiyah Bandung - Sidik, Ahmad; Fitriyani, Sani (Barongko: Jurnal Ilmu Kesehatan, 2024)
This research aims to build a management information system in logistics management at the hospital and also to evaluate the role of logistics information systems in supporting operations. The benefit is that it can help in overcoming the problem of delays in sending information data. The method used in this research is descriptive qualitative research. Data was collected through in-depth interviews with logistics managers. Data analysis shows that the Logistics Management Information System provides significant benefits in terms of transparency, accuracy, and operational efficiency. In this study the authors found several problems, namely: (1) In using SIRS, there are still many staff who do not understand how SIRS works (2) Devices in the hospital, especially computers in the logistics area, need to be updated (3) There is no significant training for staff, this makes it difficult for staff to adapt to new things. Based on the above problems, the authors try to provide several suggestions, namely: (1) The hospital should bring in people who are able to operate SIRS to teach staff so that staff understand how to use SIRS (2) Computer devices in logistics must be replaced and updated so that they are not slow, making the use of SIRS smooth (3) Hospitals should conduct gradual training for their special staff in logistics so that those who do not understand become aware and work becomes faster and more efficient.